Women's Rights and Gender Equality: An Analysis of Jasser Auda's Thoughts and His Contribution to Renewal of Islamic Family Law in Indonesia - Utsany, Royan; Tw, Afrizal; Khamim, Khamim (Institut Agama Islam Negeri (IAIN) Pontianak, 2022)
There are still many practices of marginalization and subordination of women. An incomplete understanding of the Qur’an and hadith is the main reason. Women have the same position as men and are elevated in status in Islam. This article aims to explain Jasser Auda’s thoughts on women and their contribution to the reform of Islamic family law in Indonesia. This paper uses bibliographic research as the primary source of Jasser Auda’s works. This study concludes that Jasser Auda’s thinking which provides equal positions between men and women, aligns with maqāsid al-syarī’ah, which was developed and combined with systems theory. Women have an equal role and position with men in the mosque, become leaders, and are given rights in reproductive health. The authors argue that Jasser Auda’s views on women have inspired several reforms in Islamic family law in Indonesia that pay more attention to women’s rights and position on an equal footing with men rather than the practice of understanding Muslim societies, which are still patriarchal.